Study of Violent Asphyxial Deaths in Raichur District of Karnataka - Sidramappa Gouda1 , Suraj2 , Gopinath M3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
On taking the consent from Head of the Department of Forensic Medicine, a retrospective study was conductedby analysing post mortem reports maintained in record section. Reports of post mortem examination donefrom 1st Jan 2017 to 31st Dec 2018 were analysed. Out of 520 cases done during this period, 105 (20.19%)were death due to asphyxia. In the same time data was also analysed with age of deceased, sex of deceased,season and manner of death. Among 105 cases of asphyxial deaths, males were more, accounting for 61 %(64) of study cases and females were 41(39%) cases. In the present study, commonest method of asphyxialdeaths was by hanging (75.1%), followed by ligature strangulation (12.3%) and 1 case each of postural andsexual asphyxia was the cause of death, accounting as a least method of asphyxia deaths. When age wiseassessment done, asphyxial deaths were most common in second and third decade of life, constituting mostof the suicidal cases. Asphyxial deaths were almost equally distributed among all seasons.